The impact of preterm birth on the cardiovascular system in young adulthood - Lewandowski, A (2013)
Advancements in clinical care have led to a growing cohort of preterm-born individuals now entering adulthood. Before birth, such adults were often exposed to a suboptimal intrauterine environment, and after delivery, key developmental stages that would normally occur in utero during the third trimester had to take place under ex utero physiological conditions. Through detailed cardiovascular phenotyping, this thesis investigates the cardiovascular changes in preterm-born young adults, utilising a cohort of individuals with data collection since recruitment at birth. The detailed perinatal information was first used to design nested case-control studies to investigate the effects of early lipid and glucocorticoid exposure on long-term cardiovascular physiology in individuals born preterm. It was demonstrated that intravenous lipid administration leads to an artificial elevation of total cholesterol levels in immediate postnatal life, which is associated with long-term changes in aortic and left ventricular function proportional to the degree of cholesterol elevation. Additionally, exposure to antenatal glucocorticoids relates to a regional increase in aortic arch stiffness in young adulthood, as well as changes in glucose metabolism. It was then shown that young adults born preterm have increased left ventricular mass, out of proportion to blood pressure, and a unique three-dimensional left ventricular geometry, with reduced systolic and diastolic function compared to term-born controls. Similarly, they also show distinct differences in the right ventricle, with increased right ventricular mass and a proportion having clinically impaired right ventricular systolic function. Finally, it was demonstrated that preterm-born individuals have increased circulating levels of antiangiogenic factors in young adulthood, which relate to capillary rarefaction and blood pressure elevation. These findings are of considerable public health relevance given that nearly 10% of births are now preterm. Understanding whether modification of these variations in cardiovascular structure and function prevent the development of cardiovascular disease in this growing subgroup of the population will be of future interest.